The Effectiveness of Intravitreal Bevacizumab with or without Triamcinolone Acetonide for Diabetic Macular Edema Treatment - سليمان يوسف; جلول قحطان; محمد روني (Latakia University Journal -Medical Sciences Series, 2021)
Purpose To study effectiveness of Intravitreal Bevacizumab 2.5mg IVB alone or Bevacizumab 1.25mg in combination with 2 mg Triamcinolone Acetonide IVTA in center-involved diabetic macular edema. Patients and methods: 61 eyes enrolled in this prospective, non-randomized, comparative study ( 36 eyes were injected with IVB, 25 eyes were injected with IVTA + IVB). Evaluation of best-corrected visual acuity BCVA, central macular thickness CMT, and intraocular pressure IOP was conducted at 4,8,12 weeks after treatment. Results: Significant CMT reduction was observed in each group along the follow-up period (P<0.001). The mean reduction of CMT was more significant in combination IVTA + IVB at 4 weeks (P<0.05). Significant BCVA improvement was observed each group along the follow-up period (P<0.001). BCVA changes between two groups were not significant different at follow-up period (P>0.05). The number of injections was significantly lower in IVTA + IVB group than IVB group (P=0.0045). One patient developed IOP raised more than 21 mmHg, which were treated with anti glaucoma medications. Conclusion: Bevacizumab 2.5mg Intravitreal injection alone or Bevacizumab 1.25mg in combination with 2 mg Triamcinolone Acetonide had significantly reduced CMT, and this effect was more significant in combination term at short term. Although treatment in both terms had significantly improved BCVA at all follow-up period with no differentiation between the two groups. The combination therapy may reduce the number of injections. Intravitreal injections were not accompanied with significant IOP increas.